Outdoor Mass Gatherings in Kansas: An Examination of Local Health Department awareness and Involvement - Horton, Bryna (My University, 2012)
Many outbreaks have occurred during mass gathering events as a result of person-to-person transmission of disease, animal-to-human transmission, and foodborne transmission. The Kansas Department of Health and Environment (KDHE) developed an interest in these types of events, referred to within this study as Outdoor Mass Gatherings (OMGs). A survey was constructed to obtain a list of OMGs per Kansas county and determine the amount of participation the Local Health Departments (LHDs) have in planning these events. One hundred three out of 105 LHDs responded to the survey. A database containing 185 OMGs was created with information about the events such as time span and location. More than half of the LHDs (n=58, 56.3%) responded that they are never notified by the event organizers when an OMG is scheduled in their counties. The majority of the LHDs (69.9%) also responded that they are never involved with the planning of an OMG; however, 61% of respondents agreed that the LHD should be involved. Based on results from the survey, KDHE recommends implementing notification processes so that LHDs, food inspectors, and other public health entities are involved in the planning of OMGs, and creating guidelines to assist LHDs in planning for those events.
Keywords: Outdoor mass gatherings; Food illness outbreaks; Biking Across Kansas; Taste of Chicago; Sasquatch Music Festival; North Carolina State Fair; Public Health (0573)